The embankment‐subsoil displacement mechanism. Issue 3 (19th February 2020) - Namdar, Abdoullah; Dong, Yun
Abstract: Seismic wave propagation at the subsoil has received noteworthy attention because it develops displacements at multiple directions. In this study, the effect of mechanical properties of the soil on lateral and vertical displacements of embankment‐subsoil was investigated through the modeling of two prototypes. Two types of soils were used in built‐up models 1 and 2. Near‐fault ground motion was applied to the model in the horizontal direction. The results showed that the lateral and vertical displacements of embankment and subsoil behaved differently at each simulated model when the model is subjected to the same seismic loading, and the lateral displacement was 10% and vertical displacement increased four times in the model made of soil A. The mechanical properties of the soil governed seismic wave propagation and resulted in developing lateral and vertical displacements. The discovery of this numerical analysis improved the selection of soil type for the seismic design of the embankment‐subsoil.